Inhibition of sonic hedgehog signaling blocks cell migration and growth but induces apoptosis via suppression of FOXQ1 in natural killer/T-cell lymphoma. (January 2018) - Liu, Pingyi; Chen, Lingling
Highlights: It was firstly investigated the underlying mechanism of FOXQ1 in NKTCL. FOXQ1 mRNA was significantly higher in NKTCL patients than healthy controls. FOXQ1 was related to Ann Arbor stage, bone marrow involvement and prognosis of NKTCL patients. Inhibiting FOXQ1 suppressed NKTCL cell growth and induced apoptosis by blocking Shh pathway. Abstract: The present study explored the effects of Forkhead box Q1 (FOXQ1) on cell proliferation, cell cycle and apoptosis via the Sonic hedgehog (Shh) pathway in Natural killer/T-cell lymphoma (NKTCL). Quantitative real time-polymerase chain reaction (qRT-PCR) was performed to detect FOXQ1 expression in 117 NKTCL patients and 120 healthy controls. Additionally, FOXQ1 expression in NKTCL cell lines (HANK-1, NK-92, SNK-6, SNT-8 and YT) was determined by western blotting and qRT-PCR. SNK-6 cells were transfected with FOXQ1-shRNA or Shh pathway inhibitor Cyclopamine/recombinant protein Shh. Cell counting kit-8 (CCK-8) and 5-bromo-2-deoxy-uridine (BrdU) incorporation assays were conducted to detect cell proliferation, flow cytometry was used to determine the cell cycle and cell apoptosis, and western blotting was used to detect protein expression. FOXQ1 expression was higher in NKTCL patients than in healthy controls, which was related to Ann Arbor stage, bone marrow involvement and the 5 year survival rate in NKTCL patients. Moreover, FOXQ1 expression, pathological type, Ann Arbor stage, B symptom and bone marrow involvement were independent risk factors in NKTCL. Shh pathway-related proteins were down-regulated after transfection of SNK-6 cells with FOXQ1-shRNA. Additionally, SNK-6 cell proliferation was greatly reduced, the cell cycle was blocked at the G0/G1 phase, and the expression of CyclinD1 and CyclinE was markedly decreased, while an increase in cell apoptosis with elevated Bcl-2-associated X protein (Bax) and Caspase-3 and reduced B-cell lymphoma/leukemia-2 (Bcl-2) were also observed. However, no significant alterations were observed between the FOXQ1-shRNA + Shh and Blank groups. The inhibition of FOXQ1 restricted NKTCL cell proliferation and growth but induced apoptosis via blocking the Shh signaling pathway.